IMPLEMENTASI PENGENDALIAN INTERNAL DALAM MENDETEKSI PENCEGAHAN FRAUD PADA RS ISLAM UNISMA - Lika Yunistiyawati; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study was conducted to determine the effect of the internal control system at the Islamic Hospital of UNISMA on fraud. This research was conducted at the UNISMA Islamic Hospital with a total of 6 informants, namely 1 main informant, 1 key informant and 4 supporting informants. Data collection in this study was done by interview, observation and documentation. The data analysis technique in this research is descriptive qualitative analysis.The results of this study indicate that internal control at the UNISMA Islamic hospital has been running well, this is indicated by the application of internal control elements whose results are visible and can be utilized. internal control at the UNISMA Islamic hospital that is able to minimize, prevent and detect fraud.Keywords : internal control, fraud prevention, UNISMA Islamic hospital